Growth, body composition, and distal intestine histology of Florida pompano Trachinotus carolinus in response to dietary inclusion of hydrolyzed salmon meal and pH adjustment. Issue 4 (2nd October 2021) - Novriadi, Romi; Rhodes, Melanie; Reis, João; Guo, Jingping; Swanepoel, Anneleen; Davis, D. Allen
ABSTRACT: In this study, we aimed to investigate the inclusion effect of hydrolyzed salmon meal (HSM) in combination with enzyme-treated soybean meal (ESBM) with or without pH adjustment to completely replace dietary FM on the growth, body composition, and the distal intestine condition of the fish. For that purpose, four experimental diets were formulated to be iso-nitrogenous and iso-lipidic and to contain 400 g kg −1 crude protein and 80 g kg −1 lipid. A reference diet contained 150 g kg −1 FM, 450 g kg −1 soybean meal (SBM), and 39.5 g kg −1 ESBM, and the second diet was formulated replacing FM with 190.6 g kg −1 ESBM. The third diet was produced by supplementing 40 g kg −1 hydrolyzed salmon meal (4% HSM) into the diet formulation at the expense of ESBM, and the fourth diet was produced similar with the third diet, but the pH of the diet was adjusted to match the value in the reference diet (4% HSMA). All test diets were supplemented with taurine at the level of 5 g kg −1 . Diets were fed to apparent satiation to triplicate groups of Florida pompano juveniles (mean weight 11.88 ± 0.18 g). After 8 weeks of growth, there were no significant differences in the final weight, percentage weight gain, thermal growth coefficient, feed intake, survival rate, and feed conversion ratio in fish offered the various diets. Nor were significant differences observed in the dry matter composition of the fish in all treatments and only minor changes in the histomorphological of distal intestine as the FM was replaced by plant ingredients. Overall, the adjustment of pH level of the diet containing 4% HSMA did not have any significant effect on the growth and physiological function of fish compared to the group of fish fed with diet without pH adjustment.